Evaluating the imazethapyr herbicide mediated regulation of phenol and glutathione metabolism and antioxidant activity in lentil seedlings - Kumar, Rajeev; Kumari, V Visha; Gujjar, Ranjit Singh; Kumari, Mala; Goswami, Sanjay Kumar; Datta, Jhuma; Pal, Srikumar; Jha, Sudhir Kumar; Kumar, Ashok; Pathak, Ashwini Dutt; Skalicky, Milan; Siddiqui, Manzer H; et al. (PeerJ, 2024)
The imidazolinone group of herbicides generally work for controlling weeds by limiting the synthesis of the aceto-hydroxy-acid enzyme, which is linked to the biosynthesis of branched-chain amino acids in plant cells. The herbicide imazethapyr is from the class and the active ingredient of this herbicide is the same as other herbicides Contour, Hammer, Overtop, Passport, Pivot, Pursuit, Pursuit Plus, and Resolve. It is commonly used for controlling weeds in soybeans, alfalfa hay, corn, rice, peanuts, etc. Generally, the herbicide imazethapyr is safe and non-toxic for target crops and environmentally friendly when it is used at low concentration levels. Even though crops are extremely susceptible to herbicide treatment at the seedling stage, there have been no observations of its higher dose on lentils (Lens culinaris Medik.) at that stage. The current study reports the consequence of imazethapyr treatment on phenolic acid and flavonoid contents along with the antioxidant activity of the phenolic extract. Imazethapyr treatment significantly increased the activities of several antioxidant enzymes, including phenylalanine ammonia lyase (PAL), phenol oxidase (POD), glutathione reductase (GR), and glutathione-s-transferase (GST), in lentil seedlings at doses of 0 RFD, 0.5 RFD, 1 RFD, 1.25 RFD, 1.5 RFD, and 2 RFD. Application of imazethapyr resulted in the 3.2 to 26.31 and 4.57-27.85% increase in mean phenolic acid and flavonoid content, respectively, over control. However, the consequent fold increase in mean antioxidant activity under 2, 2- diphenylpicrylhdrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assay system was in the range of 1.17-1.85 and 1.47-2.03%. Mean PAL and POD activities increased by 1.63 to 3.66 and 1.71 to 3.35-fold, respectively, in agreement with the rise in phenolic compounds, indicating that these enzyme's activities were modulated in response to herbicide treatment. Following herbicide treatments, the mean thiol content also increased significantly in corroboration with the enhancement in GR activity in a dose-dependent approach. A similar increase in GST activity was also observed with increasing herbicide dose.
Keywords: Glutathione; Flavonoids; Antioxidants; antioxidancia; flavonoidy; Phenols; Lens Plant; fenoly; zemědělské plodiny; Crops, Agricultural; semenáček; Imazethapyr; Lentil; Herbicide; herbicidy; glutathion; Phenolic acid; Herbicides; čočka; Seedlings; Phenol; fenol